Optimization and preparation of a compound cod liver oil film former agent: an orthogonal design - He, Yao; Zhang, Ying; Li, Zheng (Frontiers in Pharmacology, 2024)
Background: Cod liver oil has anti-inflammatory properties and could help regulate recurrent aphthous stomatitis (RAS). An orthogonal experiment was used to evaluate and improve the dosage form of compound cod liver oil, which has replaced the previously used liniment preparation based on film method. Methods: An orthogonal experiment was adopted, and the appearance and film-forming time of the film coating agents were used as indicators. The optimal ratio in the preparation process for the compound cod liver oil film agent was then optimized. A method for determination of compound cod liver oil film was established using High-Performance Liquid Chromatography (HPLC). Results: The results indicate that the blank films prepared using 55 mg polyvinyl alcohol (PVA) (PVA low), 45 mg of PVA (PVA medium), and 10 mg glycerol had the optimal performance, which was defined as PVAa. The drug-carrying film prepared from 3 mL PVAa (i.e., film-forming material with the optimal proportion), 30 mg dexamethasone acetate, and 30 mg metronidazole had the optimal performance. The verified sample has a complete and smooth appearance, uniform thickness and color, and no evident bubbles, which meets the requirements for a film agent defined in the Chinese Pharmacopoeia, 2020 edition. HPLC was used to determine the major components: dexamethasone acetate, metronidazole, and dyclonine hydrochloride, and the optimal separation effect was obtained. The method has advantages of good specificity, good linear results, high recovery rate, and good repeatability. Conclusion: This study proposes an optimized compound cod liver oil film former agent and preparation method. The results indicate that the compound cod liver oil film former agent had good performance, reflecting the high feasibility of this research method. The detection method of compound cod liver oil film was established by HPLC. The method was feasible, and the validity and stability of the formulation and preparation technology were guaranteed. The role of the newly developed agent in patients with RAS should be investigated further.